A Foresight Study on the Adoption of Autonomous Public Transport in Malaysia: Case Study in Kuching - Sylvester Kuan Wee Seong; Shamsuddin, Alina (Research in Management of Technology and Business, 2023)
Autonomous vehicles are getting common and being a hot topic in this technological era. However, autonomous public transport is still new phenomenon in Malaysia. As a result, there is uncertainty over the adoption of autonomous public transport. The question arises as to whether a combination of automated driving and public transportation is a flexible and efficient mobility option that may also attract former non-customers to use public transportation in Malaysia. Hence this study is aimed to identify the drivers, the level of consumer perceptions, and future trends of the autonomous public transport in Malaysia. Social, Technological, environmental, Economic, Political, Value (STEEPV) analysis is used in the first phase for identifying the issues and drivers of adopting autonomous public transport in Malaysia. The impact-uncertainty of autonomous public transport in Malaysia is analysed using questionnaire distribution and SPSS statistical analysis in the second phase. A total amount of 382 questionnaires were distributed to the community in Kuching. 211 responses were gathered and the response rate was 55.23%. Based on the impact-uncertainty analysis, the results show that the two drivers with highest impact and uncertainty were government policy and effective and efficient of autonomous public transport. The scenario analysis was constructed with the two drivers which illustrates the four alternative possibilities in the future. The ideal scenario is where government policy and effective and efficient must coexist in order to generate positive future for adoption of autonomous public transport in Malaysia.